Mancal magnético supercondutor com laços de fitas de segunda geração - Martins, Flávio Goulart dos Reis (2018)
This thesis aims to demonstrate a novel design of superconducting coils using second generation tapes as persistent currents loops, called the Double Crossed Loops. In this work it is proposed to use them in the new levitation system for the MagLev Cobra vehicle. A simulation model using Integral Equations solved by finite elements in commercial software COMSOL was developed. Also a manufacturing procedure for these coils is proposed, from their design, preparation until impregnation. Small scale prototypes were built and experimentally analyzed by vertical force measurements to validate the simulations results. In addition, experimental results were compared to the present levitation system. The prototypes have presented forces comparable to the existing levitation system, leading to the conclusion that the novel coil design, the simulation model and manufacturing technique were successful.